MÍDIA E COMUNIDADE: estudo sobre produção e recepção da rádio Heliópolis FM - Afonso, Maria Rita Teixeira (2007)
The research is a study about output and reception of the radio Heliópolis FM, by his public, Heliópolis s inhabitants. The objective was understand how radio is perceived by his public. The study was divide in two phases. The first is based in bibliographical research. In the following phase, rescues-itself the transcript of the sender and verifies-itself the appropriation of the Heliópolis FM by inhabitants and itself to communal paper perform sender, investigating itself as to radio is appropriated by his assiduous listeners. The approach to the reception was deed having for base the theoretical-methodological slope of the social use of the means, of Jesús Martín-Barbero. This kind of study consists of the displacement of the space of interest of the means for the place where is produced his sense social movements and, of a special way, of those that start from the neighborhood (1997). To technical it used was the interview is structured. I concluded that to radio is perceived as communal by his receivers mainly because opens space for the local population produce programs, choose the song that will be touched, present his works and utilize his service like the of location of persons and documents lost freely.(AU)